2022
DOI: 10.1088/1674-1056/ac2487
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermoelectric performance of PEDOT: PSS films via ionic liquid post-treatment

Abstract: Thermoelectric (TE) energy harvesting can effectively convert waste heat into electricity, which is a crucial technology to solve energy concerns. As a promising candidate for energy conversion, poly(3,4-ethylenedioxythiophene): poly (styrene sulfonate) (PEDOT:PSS) has gained significant attention owing to its easy doping, high transparency, and solution processability. However, the TE performance of PEDOT:PSS still needs to be further enhanced. Herein, different approaches have been applied for tuning the TE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…The PEDOT:PSS dispersion after evaporating water does not form a flat film on the Teflon mold. However, the film-forming ability is acquired after Li-TFSI doping, and the formed flat films have good toughness. , The doping causes a morphological rearrangement in favor of PEDOT chain packing, as demonstrated by a newly formed X-ray diffraction (XRD) peak at a diffraction angle of 12.12° and sharpened intrinsic peaks at 18.08 and 25.88° (Figure S6). , The intrinsic peaks also appear in the pure PEDOT:PSS film.…”
Section: Resultsmentioning
confidence: 99%
“…The PEDOT:PSS dispersion after evaporating water does not form a flat film on the Teflon mold. However, the film-forming ability is acquired after Li-TFSI doping, and the formed flat films have good toughness. , The doping causes a morphological rearrangement in favor of PEDOT chain packing, as demonstrated by a newly formed X-ray diffraction (XRD) peak at a diffraction angle of 12.12° and sharpened intrinsic peaks at 18.08 and 25.88° (Figure S6). , The intrinsic peaks also appear in the pure PEDOT:PSS film.…”
Section: Resultsmentioning
confidence: 99%
“…The variance in the amplitude of polarization transitions indicated that ILs featuring smaller‐sized cations exhibited a more potent reducing effect. [ 100 ] A substantial improvement in conductivity was realized through intensive mixing of PEDOT:PSS solutions with IL containing bis(trifluoromethylsulfonyl)imide (TFSI) anions. [ 87 ] By altering the cation from (2‐(2‐ethoxyethoxy)ethyl)triethylphosphonium (P2EOE) (conductivity: ≈ 8 S cm −1 ) and (2‐ethoxyethyl)triethylphosphonium (PEOE) (conductivity: ≈ 16 S cm −1 ) to EMIM (conductivity: ≈ 220 S cm −1 ) and finally to Li + (conductivity: ≈ 420 S cm −1 ), the most effective among the series, there was an enhancement in crystalline order and p‐doping level of PEDOT, leading to higher conductivity.…”
Section: Selection Principles Of Ilsmentioning
confidence: 99%